Development and evaluation of an implementation strategy to increase HPV vaccination among underserved youth across Texas: a protocol paper - Paula M. Cuccaro; Jihye Choi; Lara S. Savas; Efrat K. Gabay; Mayra Aguilar McBride; Amy Montelongo Eldridge; Timothy J. Walker (Implementation Science Communications)
Abstract Background All for Them is a theory-based and evidence-informed multilevel, multicomponent program delivered through schools to increase HPV vaccination among medically underserved youth across Texas. Given the potential logistical challenges of program implementation, understanding how to best support the implementation and sustainment of the program is critical. The overall goals of this study are twofold: 1) develop a multifaceted implementation strategy, Implementing All for Them (IM-AFT); and 2) evaluate the impact of IM-AFT on implementation outcomes for schools and healthcare providers to successfully implement All for Them in their respective settings. Methods This study is underpinned by a comprehensive and synergistic conceptual framework. We will use Social Cognitive Theory and the Interactive Systems Framework for Dissemination and Implementation to inform important individual and organizational factors to target as part of implementation strategy development. We will use this formative work and Implementation Mapping, a systematic, iterative process that guides the use of theories, models, and frameworks, to develop IM-AFT. The three core aims of the present study are connected to the five tasks of Implementation Mapping. For Aim 1, we will develop IM-AFT using a community-based participatory research-informed approach, including a qualitative assessment of needs and assets associated with program implementation and identification of behavioral and psychosocial objectives to determine implementation outcomes. For Aim 2, we will use a mixed-methods approach to assess user experience with the IM-AFT prototype to test its feasibility, usability, and acceptability. For Aim 3, we will use a descriptive checklist to assess the impact of IM-AFT on user fidelity of program implementation. Discussion This paper presents the detailed protocol for developing and evaluating IM-AFT to successfully implement All for Them, leveraging a systematic, community- and theory-based approach and user experience with the strategy prototype. This study will contribute to expanding limited scientific knowledge about using multiple sources to develop and evaluate specified implementation strategies for effective implementation of school-based vaccination programs. Theory-based IM-AFT will guide collaborations between schools and community health centers to improve HPV and other adolescent vaccination rates in underserved communities in Texas.